Wing patterns of ditrysian moths (Lepidoptera: Psychidae) include variants and violations of predictive models. Issue 3 (5th June 2017) - Schachat, Sandra R; Brown, Richard L
Abstract: Although the evolution of wing pattern in Lepidoptera is of great importance in various disciplines, potential wing pattern homologies have been examined in very few lineages of microlepidoptera. Psychidae belong to the most early‐diverging superfamily of ditrysian moths, and many psychid genera from Australia have wing patterns consisting of bands, spots, and/or reticulated lines. An examination of 35 species of Australian Taleporiinae (Psychidae) revealed that wing patterns most commonly conform to the 'uniform wing‐margin' model, in which each vein is surrounded by a pattern element of the same colour (usually dark brown) along the costal margin. Wing patterns that follow the 'uniform wing‐margin' model include bands, spots, and reticulated lines, suggesting that these pattern elements are homologous in some lineages. However, in patterns consisting primarily of spots (belonging to the genus Iphierga Meyrick), the spots can become smaller toward the distal portion of the wing, often disappearing altogether and thus causing an apparent violation of the predictions of the model. The wing patterns of three species clearly violate the 'uniform wing‐margin' model. Two of these three may conform to the 'alternating wing‐margin' model, though this is uncertain because some veins are not expressed in the adult wing. Lastly, the findings presented here demonstrate that for the 'uniform wing‐margin' model, as for the 'alternating wing‐margin' model, the relative colour of a series of pattern elements (dark vs. light) is not a reliable indicator of homology. Instead, homologies exist among the contrast boundaries that separate pattern elements.